-28=-7x-2(-5x+23)

Simple and best practice solution for -28=-7x-2(-5x+23) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28=-7x-2(-5x+23) equation:


Simplifying
-28 = -7x + -2(-5x + 23)

Reorder the terms:
-28 = -7x + -2(23 + -5x)
-28 = -7x + (23 * -2 + -5x * -2)
-28 = -7x + (-46 + 10x)

Reorder the terms:
-28 = -46 + -7x + 10x

Combine like terms: -7x + 10x = 3x
-28 = -46 + 3x

Solving
-28 = -46 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-28 + -3x = -46 + 3x + -3x

Combine like terms: 3x + -3x = 0
-28 + -3x = -46 + 0
-28 + -3x = -46

Add '28' to each side of the equation.
-28 + 28 + -3x = -46 + 28

Combine like terms: -28 + 28 = 0
0 + -3x = -46 + 28
-3x = -46 + 28

Combine like terms: -46 + 28 = -18
-3x = -18

Divide each side by '-3'.
x = 6

Simplifying
x = 6

See similar equations:

| 4(2-y)+3y=3(y-4) | | 16-8a=2a | | -11m+1=-10m+18 | | 8(7n-4)=-144 | | 8-n=3(2n-4) | | -11m+1=-10+18 | | -1/2(8x+2)+1/5(35x+10) | | 4b-7=20+4b | | (4u-5)(3+u)=0 | | 6b^2+23=11 | | 40/4=5x+2(-4x) | | 5/4(x+2)=3 | | 5w+41=3(w+9) | | 0.333333(x+3)+0.1666666(x-6)=x+3 | | (4x+1500)-(2x+1800)=0 | | -4/3x^2-19/18x-19/36=0 | | 2y+3=3(7+7) | | G+2(3+g)=4(g+1) | | 2=400/x | | (x+5y)dy=-(2x+3y)dx | | 7=5(x+5)-7x | | onethird(x+3)+onesixth(x-6)=x+3 | | 5xa-7a^2=2a^2+2ax | | -6x-3(7x-26)=-111 | | 4a-2a+11=6a-13 | | 9w+5= | | 5ax-7a^2=2a^2+2ax | | 8(-7+8v)=200 | | 9w-5= | | 1p-15=13-6p | | 10p+6=-18-2p | | 29=4x-5 |

Equations solver categories